Narrating the Holocaust. - Reiter, Andrea, 1957-2018 (Continuum Collection., 2004)
In this literary study of memoirs describing at first hand the horrors of German concentration camps, the principal question asked is: How did the survivors find the words to talk about experiences hitherto unknown, even unimaginable? Beyond being a mere analysis of discourse, Narrating the Holocaust reflects the situations in camp that triggered these responses, and shows how the professional authors adapted certain literary genres (e.g. the travel story, the Hassidic tale) to serve as models for communication, while the vast majority who were not trained as writers merely used the form of th.